2007
DOI: 10.17239/l1esll-2007.07.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Early writing development in L1 English speaking children

Abstract: Abstract. This paper reports on the developmental and psychometric properties of an early writing task. The study was carried out over four years in Toronto, Canada with L1 English-speaking children. Two cohorts of children who began in Nursery School were followed to the end of their Grade 1 year. Children were administered the same writing task at four time points along with standardized measures of early reading. The early writing task required children to write words and number and word combinations; we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In studies on the acquisition of writing in English Cassar 1996, 1997;Nunes, Bryant and Bindman 1997;Byrne, 1998;Treiman, 1993Treiman, , 2004Ehri 2000;Bourassa & Treiman, 2001;Pelletier & Lasenby, 2007), it was shown that morphological and orthographic awareness develops along with reading and writing instruction, yet children are able to use the knowledge on orthographic models of their native language very early (they know which letters tend to be doubled, which letters never occur at the beginning, etc. ), and also use morphological knowledge in order to support their spelling.…”
Section: Spelling Acquisition By Polish and English Childrenmentioning
confidence: 99%
“…In studies on the acquisition of writing in English Cassar 1996, 1997;Nunes, Bryant and Bindman 1997;Byrne, 1998;Treiman, 1993Treiman, , 2004Ehri 2000;Bourassa & Treiman, 2001;Pelletier & Lasenby, 2007), it was shown that morphological and orthographic awareness develops along with reading and writing instruction, yet children are able to use the knowledge on orthographic models of their native language very early (they know which letters tend to be doubled, which letters never occur at the beginning, etc. ), and also use morphological knowledge in order to support their spelling.…”
Section: Spelling Acquisition By Polish and English Childrenmentioning
confidence: 99%
“…In this task (Pelletier & Lasenby, 2007), children are asked to write a short sentence including numbers and words, for example, "Teacher has five little red crayons," using their choice of colored markers, pencil crayons, and lead pencils. Scores on the writing portion of this task range from 1 (for scribble) to 13 (for correct spelling).…”
Section: Print Task (Early Writing)mentioning
confidence: 99%
“…When a four-year-old girl wrote in her grandmother’s birthday card “HP BrDA NNe” ( Happy Birthday Nanny ), she was using ‘invented spelling’ (Chomsky, 1971; Ouellette and Sénéchal, 2008b; Read, 1971; Tangel and Blachman, 1992). The examination of children’s early spelling and writing indicates that these abilities typically progress from drawing or scribbling as a means of representing language graphically, to using letters to represent and spell words (Pelletier and Lasenby, 2007; Puranik and Lonigan, 2012; Tangel and Blachman, 1992, 1995; Treiman and Bourassa 2000). The skills and knowledge considered to be developmental precursors to conventional spelling are believed to change as children’s spelling becomes more accurate and refined (Kaderavek et al., 2009; Milburn et al., 2015; Pollo et al., 2008; Shatil et al., 2000).…”
mentioning
confidence: 99%